GENE-31. MULTIPLATFORM MOLECULAR PROFILING AND QUANTITATIVE IMAGING OF AN ANAPLASTIC EPENDYMOMA REVEALS INTRATUMORAL HETEROGENEITY. (5th November 2018) - Magill, Stephen; Liu, John; Vasudevan, Harish; Hilz, Stephanie; Ferris, Sean; Ann, Nancy; Bush, Oberheim; Villanueva-Meyer, Javier; Bollen, Andrew; Costello, Joseph; McDermott, Michael; Raleigh, David
Abstract: OBJECTIVES: Ependymomas are associated with distinct anatomic, genomic and clinical characteristics, but the diversity of molecular features within individual ependymomas is incompletely understood. Here, we perform multiplatform molecular profiling from 6 spatially- and radiographically-distinct regions within a single anaplastic ependymoma to shed light on intratumoral heterogeneity. METHODS: Immunohistochemistry, UCSF500 sequencing, whole exome sequencing, 850k DNA-methylation profiling and RNA-sequencing were performed to define the genomic, epigenomic and transcriptomic characteristics of stereotactically-collected samples that were separated by an average 19 mm (range 6–34 mm). Data were analyzed using hierarchical clustering, principal component analysis, molecular phylogenetic approaches, and multi-parametric radiologic techniques. RESULTS: Immunohistochemistry revealed diffuse L1CAM positivity, and UCSF500 detected chromosome 11 chromothripsis, suggestive of C11orf95-RELA fusion. All 6 regions expressed equivalent ependymoma markers such as L1CAM and CCND1 byRNA-sequencing, which also confirmed C11orf95-RELA fusion. Principal component analysis of transcriptomic data identified three transcriptionally distinct tumor regions that were delineated by stem/proliferative genes ( HOXB3, OLIG2, PTPRN2 ), neuronal differentiation genes ( DLK1, LBX1, HDAC9 ) or immune/stress response genes ( CXCL8, HSPA1B, VEGFA ). DNA methylation analysis was consistent with C11orf95-RELA fusion ependymoma, but also identified three epigenetic profiles with similar characteristics to those discovered by RNA-sequencing from different tumor regions. Whole exome sequencing identified shared SETD2 and IL5RA mutations throughout the tumor, as well as private mutations specific to individual regions, including MUC4, ZNRF3 and TGFBR2 . Stem/proliferative regions were additionally characterized by SETD2 deletion and increased cerebral blood flow relative to other regions by magnetic resonance perfusion. CONCLUSION: Anaplastic ependymoma is associated with a previously unappreciated molecular heterogeneity that may influence tumorigenesis and design of molecular therapeutics.